2018
DOI: 10.1161/jaha.118.009636
|View full text |Cite
|
Sign up to set email alerts
|

CD40L Priming of Platelets via NF‐κB Activation is CD40‐ and TAK1‐Dependent

Abstract: Background CD40 ligand (CD40L) is a thromboinflammatory molecule that predicts cardiovascular events. CD40L is a strong activator of nuclear factor kappa B (NF‐κB) in platelets that primes and enhances platelet activation in response to thrombotic stimuli. In addition to its classical receptor CD40, CD40L binds αIIbβ3, α5β1, and αMβ2 in various cell types. However, the function of the different CD40L receptors on platelets remains unexplored. The present study aims to identify the receptors of CD4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 60 publications
1
22
0
Order By: Relevance
“…Therefore, a more plausible result would necessitate the stimulation of IKK inhibitor VII-pretreated platelets with a priming/sub-optimal dose of those agonists, in order to better observe the potentiating effect of the inhibitor. In this context, our recent study demonstrated that the aggregation of platelets pretreated with BAY 11-7082 or TAK-1 inhibitors, 5Z-7-Oxozeaenol and Takinib, primed with sCD40L, and then stimulated with sub-optimal doses of thrombin was abrogated completely [95]. Our results also pinpointed the emerging importance of TAK-1 in NF-κB activation in platelets as another attractive therapeutic target in thrombotic diseases.…”
Section: Nf-κb Functions In Plateletssupporting
confidence: 62%
See 3 more Smart Citations
“…Therefore, a more plausible result would necessitate the stimulation of IKK inhibitor VII-pretreated platelets with a priming/sub-optimal dose of those agonists, in order to better observe the potentiating effect of the inhibitor. In this context, our recent study demonstrated that the aggregation of platelets pretreated with BAY 11-7082 or TAK-1 inhibitors, 5Z-7-Oxozeaenol and Takinib, primed with sCD40L, and then stimulated with sub-optimal doses of thrombin was abrogated completely [95]. Our results also pinpointed the emerging importance of TAK-1 in NF-κB activation in platelets as another attractive therapeutic target in thrombotic diseases.…”
Section: Nf-κb Functions In Plateletssupporting
confidence: 62%
“…In platelet physiology, our laboratory showed that CD40L alone induced IκBα phosphorylation and NF-κB activation exclusively through platelet CD40 receptor [95]. We also showed that sCD40L, in the presence of sub-optimal doses of platelet agonists like collagen and thrombin, significantly increased platelet activation and aggregation through an NF-κB-independent CD40/TRAF-2/Rac-1/p38 MAPK axis [9].…”
Section: Nf-κb Functions In Plateletsmentioning
confidence: 99%
See 2 more Smart Citations
“…The classical activation of NF-κB needs the 26 s proteasome induced ubiquitination and degradation of IKBa, NF-κB is then released from the cytoplasmic NF-κB/IkBa complex, and exposing the nuclear localization domain, forming a p50/RelA dimer, activating the transcription of tumor-related factors downstream. Additionally, NF-κB also can be activated in other ways such as nucleolar stress, tumor necrosis factor receptor (TNFR) family ligands CD40L [43], ROS [44], and angiotensin [45].Thus the inhibition of NF-κB activity is considered to be one promising strategy to manipulate the tumorigenesis and development of cancers.…”
Section: Commd7 Enhanced Hepatoma Cell Proliferation Through Activatimentioning
confidence: 99%